Profile of Upper Extremities Function among Stroke Outpatients in Dr. Hasan Sadikin General Hospital, Bandung - Putri Pamulani; Novitri Novitri; Sofiati Dian (Althea Medical Journal, 2020)
Background: Stroke is one of the leading causes of death and disabilities worldwide. Among all types of disabilities, disturbance in upper extremities functions is at the highest percentage. This study aimed to determine the profile of upper extremities function among stroke outpatients in Dr. Hasan Sadikin General Hospital as an initial step to provide a better follow up and management.Methods: The design of this study was a descriptive study, conducted from April to October 2014 among stroke outpatients in the Department of Physical Medicine and Rehabilitation Dr Hasan Sadikin General Hospital, Bandung based on a consecutive sampling method. The function of upper extremities was tested by Chedoke Arm and Hand Integrated version 9 (CAHAI-9).Result: In total, 42 patients were included, consisting of a male (n=25) and a female (n=17). Nine tasks were performed with dependently by the patients such as open the coffee jar (n22; 52%), call 118 (n24;57%), draw a line with a ruler (n22;52%), pour a glass of water (n33;79%), wring out washed cloth (n26;62%) do up five-button (n31;74%), dry back with the towel (n25;60%), put toothpaste on a toothbrush (n25;60%), and cut medium resistance putty(n32;76%).Conclusions: The majority of stroke outpatients in the sub-acute phase still have a dependent function of upper extremities. Better patient management and interventions focusing on this function need to be enhanced for a better outcome.